MORAL VALUES IN THE LEGEND OF TUNGGANG PARANGAN IN KUTAI LAMA EAST KALIMANTAN - Ardelia, Azra Abidah; Putri, Nina Queena Hadi (UNIVERSITAS PGRI YOGYAKARTA, 2025)
ABSTRACT The Kutai Lama community has a diversity of regional oral literature that is rich in moral values, one of which is legend. Legends not only tell the origin of a place, but also contain valuable life lessons for the community. One of the legends originating from Kutai Lama is the legend of Tunggang Parangan. This study aims to describe the form of moral values in the legend of Tunggang Parangan in Tepian Batu Hulu Dusun Jaitan Layar, East Kalimantan. The research method used in this study is a qualitative method using an ethnographic approach. This technique was carried out by observing and interviewing informants at Tepian Batu Hulu Jaitan Layar Hamlet, Kutai Lama, East Kalimantan related to the legend of Tunggang Parangan. The data analysis technique in this study was carried out with the Miles and Huberman model which was carried out with four stages of activities, namely data collection, data reduction, data presentation, conclusion drawing. The results showed the form of moral values contained in the legend of Tunggang Parangan, namely: (1) The form of moral values in human relations with oneself includes courage, trustworthiness, and never giving up (2) The form of moral values in human relations with other humans in the social sphere and the natural environment includes working hard and helping. (3) The form of moral values in human relationships with God includes believing in God and worshiping. Keywords: legend, value, moral, Kutai Lama, form of moral value